(untitled) (REVISTA NODO, 2026)
In this essay, I analyze the relationship between performing arts (in this case, contemporary dance) and a synchronic materialization that produces something distinct, traditionally located within the visual arts. The relationship between the ephemeral and the material, in the media of dance and drawing, initially unfolds within a performative and creative space while simultaneously generating clearly differentiated medial spaces. The essay focuses on the gaze in multiple manifestations: in the observation and materialization of the ephemeral (dance) observed by the artist; in the gaze as a conceptual metaphor; and in the way it shapes the archive under construction. This archive is based on the legacy of the visual artist, painter, videographer, and scenographer Eduardo López Lemus, and includes his works and observations (again, as a specific gaze), as well as reflections on the conceptualization of the archive itself. Once again, we encounter the presence of the gaze, now in the form of visual concepts, exemplified by second-order observation transformed into action, and absence as a problem of representation.